The Influence of Experiential Marketing and Emotional Marketing on Customer Loyalty at Starbucks Jemursari - Asyhari, Muhammad Daffa; Dermawan, Rizky (International Journal of Economics (IJEC), 2024)
Experiential Marketing is a way of providing customers with experience regarding the services or products they use so as to influence customer loyalty. Emotional Marketing aspects build emotional relationships beyond the experiences experienced by customers, warm emotional relationships build customer attachment to products or services. This research aims to determine the influence of Experiential Marketing and Emotional Marketing on customer loyalty at Starbucks Jemursari. This research method uses quantitative research. The population in this research is Starbucks Jemursari customers with a total of 103 respondents. The sampling technique uses a non-probability sampling method with purposive sampling technique. The analysis technique for this research uses the partial least squares (PLS) method. The research results show that Experiential Marketing has an effective influence on customer loyalty at Starbucks Jemursari and Emotional Marketing has an effective influence on customer loyalty at Starbucks Jemursari.